Electronic Charge Transport in Extended Nematic Liquid Crystals - Woon, K.L.; Aldred, M.P.; Vlachos, P.; Mehl, G.H.; Stirner, T.; Kelly, S.M.; O'Neill, M. (American Chemical Society, 2006)
We report a systematic study of charge transport in a range of low-molar-mass and extended (having at least six aromatic rings) nematic liquid crystals, some of which are reactive mesogens, with a high degree of shape anisotropy, i.e., the length-to-width (aspect) ratio is exceptionally high. We demonstrate that the hole mobility is independent of the macroscopic, but not microscopic, ordering of the nematic and isotropic phases of these nematic liquid crystals with a long, rigid, and extended aromatic molecular core, because no discontinuity is observed at the transition between these phases. A room-temperature mobility of up to 1.0 × 10-3 cm2 V-1 s-1 is obtained in the nematic phase, which is attributed to the short intermolecular distances between the highly polarizable but rigid long aromatic cores. We show that the intermolecular separation can be easily fine-tuned by changing the lateral and terminal aliphatic groups of these nematic liquid crystals. Hence, the charge mobility can be varied by up to 2 orders of magnitude without altering the core structure of the molecules, and this chemical fine control could be used to limit hole transport and so provide better charge balance in organic light-emitting diodes. X-ray diffraction is used to obtain the intermolecular separation and shows local lamellar order in the nematic phase.